2015
DOI: 10.1371/journal.pntd.0004141
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Geographic Distribution of Mycobacterium leprae SNP Genotypes Determined for Isolates from Leprosy Cases Diagnosed in Metropolitan France and French Territories

Abstract: BackgroundBetween 20 and 30 bacteriologically confirmed cases of leprosy are diagnosed each year at the French National Reference Center for mycobacteria. Patients are mainly immigrants from various endemic countries or living in French overseas territories. We aimed at expanding data regarding the geographical distribution of the SNP genotypes of the M. leprae isolates from these patients.Methodology/Principal findingsSkin biopsies were obtained from 71 leprosy patients diagnosed between January 2009 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In summary, branch 4 strains seem to be restricted to West Africa, whereas branches 2E, 2F, and 2H are present in East Africa, including Ethiopia (2E, 2F, and 2H) and Malawi (2E) (Monot et al, 2009;Benjak et al, 2018). Strains from branches 1 and 2 have been reported in the Congo (Reibel et al, 2015), while branch 3 strains, notably of genotype 3I, have been described in Morocco and Egypt (Monot et al, 2009). The canonical SNP type 1D is found in 12 countries outside Africa (Monot et al, 2009;Benjak et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In summary, branch 4 strains seem to be restricted to West Africa, whereas branches 2E, 2F, and 2H are present in East Africa, including Ethiopia (2E, 2F, and 2H) and Malawi (2E) (Monot et al, 2009;Benjak et al, 2018). Strains from branches 1 and 2 have been reported in the Congo (Reibel et al, 2015), while branch 3 strains, notably of genotype 3I, have been described in Morocco and Egypt (Monot et al, 2009). The canonical SNP type 1D is found in 12 countries outside Africa (Monot et al, 2009;Benjak et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…In Madagascar and the Comoros, little is known about the genetic background of circulating M. leprae strains. Two epidemiological studies reported the presence of the genotype 1D in Madagascar, but only seven isolates were studied so far (Monot et al, 2009;Reibel et al, 2015). No information is available about the strains currently circulating in the Comoros.…”
Section: Introductionmentioning
confidence: 99%
“…Great Britain, Germany, Switzerland and France have been free of autochthonous human leprosy cases for decades or even centuries (14, 25–27), while autochthonous cases have been noted in more recent times in Italy (28). There are no obvious reasons why continental Eurasian red squirrels are less likely to have had contact with leprosy bacilli from a human source in the past than British squirrels, especially in countries where autochthonous human cases, albeit rare, still appear.…”
Section: Discussionmentioning
confidence: 99%
“…One Mycobacterium leprae infection was acquired in the Comoros. A French study conducted from 2009 to 2013 reported that the Comoros were the main focus of Mycobacterium leprae infections diagnosed in France [24], while in a study conducted in Madrid, from 1989 to 2015, most cases were migrants from South America [25] and in a Danish study conducted from 1980 to 2010, most cases were migrants from South-East Asia [26]. In our study, one Bartonella henselae case was diagnosed in a patient returning from Morocco, a disease rarely described in Morocco [27][28][29][30], while fleas have been shown to be positive for Bartonella henselae in this country [31].…”
Section: Discussionmentioning
confidence: 99%